Evaluation of Internalized Stigma and Quality of Life of Patients with Psoriasis - Demirkiran, Bedriye Cansu; Kiyak, Emine (Makara Journal of Health Research, 2022)
Background: Internalized stigma is defined as individuals’ acceptance of negative stereotypes created by society and then their alienation from society. Psoriasis is a dermatological disease that affects the quality of life. The study evaluated the internalized stigma and quality of life of patients diagnosed with psoriasis. Methods: This cross sectional study enrolled 222 patients. Data were collected using the internalized stigma scale and the dermatology life quality index questionnaires. Data were analyzed using the Cronbach’s alpha. Results: The internalized stigma score of the patients was 78.41 ± 23.14, and the quality of life score was 12.30 ± 5.67. Stigmatization and quality of life were affected by patients’ physical, psychological, and social lives (p < 0.05). Conclusions: Patients’ internalized stigma level was high, their quality of life was low, and their quality of life decreased as the internalized stigma level increased. Furthermore, the internalized stigma level of the patients who suffered more from psoriasis was higher, but their quality of life was lower than those who suffered less.